Implementing Project-Based Learning to Enhance Critical Thinking Skills in High School Students - Taufik Huda; Abdul Malik; Nurani Ai Erlinawati; Andhika Lungguh Perceka; Yance Manoppo (International Journal of Educational Research Excellence (IJERE), 2024)
The objective of this study is to ascertain student responses and enhance their critical thinking abilities through the implementation of project-based learning models at SMA 6 Jakarta. To achieve these objectives, this research was conducted using the qualitative method. This study focused on 19 students at SMA 6 Jakarta. It examined the application of a project-based learning model and related factors, including students' responses, their critical thinking abilities, implementation constraints, and efforts to address these issues. Data were gathered through a combination of methods, including observation, in-depth interviews, focus group discussions, document recording, questionnaires, and critical thinking tests. The resulting data were analyzed both quantitatively and qualitatively. The findings indicated that implementation of learning at SMA 6 Jakarta using a project-based learning model has led to notable improvements in students' critical thinking abilities. Additionally, the student response to the learning process was largely positive.